Improvement in quality of life and loneliness after the community connections program: a community-based pilot intervention in South Australia - Bryony Jardine; Pei Jie Tan; Ashleigh Powell; Diana Eyers-White; Catherine Mackenzie; Ian Goodwin-Smith; Sandra Robinson; Penny Baldock; Mia Zaccardo; Celina Valente; Camilla Trenerry; Svetlana Bogomolova (BMC Psychology)
Abstract Background Reducing loneliness and enhancing quality of life (QoL) are key public health priorities. However, limited empirical research examines the impact of community-based interventions on both loneliness and QoL. This study employed a single-group pre-post design to evaluate the South Australian pilot intervention, the Community Connections Program (CCP), assessing its effects on participants’ self-reported QoL and loneliness. Methods Individuals referred to the CCP pilot completed an interviewer-led survey at both intervention intake and completion. QoL was assessed with the Assessment of Quality of Life – 6 dimensions tool (AQoL-6D). Loneliness was assessed with the Campaign to End Loneliness Tool – 3-item measure (CtELT). Data were analyzed using descriptive statistics and paired sample t-tests. Results Data from 195 adults who completed both data collection points were evaluated. AQoL-6D improved from intervention intake (M = 57; SD = 16) to completion (M = 66; SD = 13) (t(194) = -9.73, p <.05; d = 0.62). All six dimensions of AQoL improved, with the greatest increase in scores occurring for mental health, relationships and coping (results were statistically significant at p <.05). The largest within-group effect size was found for the dimension of mental health (d = 0.8). Participants’ overall feelings of loneliness significantly decreased between pre- (M = 6.7; SD = 2.99) and post- (M = 4.4; SD = 2.00) intervention measurement (t(186) = 10.50, p <.05; d = 0.90). Conclusions Participants of the CCP pilot intervention reported significantly improved QoL and reduced loneliness at program completion. The CCP shows promise for the ability of community-based interventions to reduce loneliness and improve QoL for individuals disconnected from their communities and local health and support care services. These findings have implications for the development of programs that facilitate place-based, person-centered connections as important drivers of public health and wellbeing.